2021
DOI: 10.1088/1755-1315/892/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

The impact of agricultural extension on productivity of smallholder sugarcane farmers in East Java

Abstract: Agricultural extension is one of the most important factors to increase smallholder sugarcane farmer capacity and encourage the acceleration of technology adoption which positively correlates with farm productivity. This study aims to evaluate the impact of agricultural extension on the productivity of smallholder sugarcane farmers in East Java. While few previous studies showing the relationships, very limited involving a relatively large number of samples. This study used data from Indonesian Plantation Farm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…A strong educational system that includes both general education classes and more specific occupational training might be considered the fundamental necessity for mass agricultural output [22,23] . Studies on the effectiveness of training for farmers have shown that only training programs that have been carefully revised and created to address specific farm needs can increase productivity in farms [24][25][26] . Based on this, it was hypothesized that:…”
Section: Development Of Research Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations
“…A strong educational system that includes both general education classes and more specific occupational training might be considered the fundamental necessity for mass agricultural output [22,23] . Studies on the effectiveness of training for farmers have shown that only training programs that have been carefully revised and created to address specific farm needs can increase productivity in farms [24][25][26] . Based on this, it was hypothesized that:…”
Section: Development Of Research Hypothesesmentioning
confidence: 99%
“…Because information can be sent across a large region at a quick and affordable rate through mass media, extension service organizations employ it. The media serves as a good source of early information for farmers and a reliable method for communicating production information on recent developments and catastrophes which greatly influences the levels of farm yields [24] . Based on this, it was hypothesized that:…”
Section: H2: Access To Government Demonstration Farms Positively Infl...mentioning
confidence: 99%
See 2 more Smart Citations
“…This is supported by the studies such as; Danso-Abbeam et al [26] who reported an increased farm production of 300 kg/ha among farmers who participated in the extension programs than those who did not. Similarly, Kosim et al [27] reported that sugarcane farmers who participated in agricultural extension programs realized 9.5 tons higher than those who did not participate. Emmanuel et al [28] also presented the benefits of extension services by reporting an increase in adoption of chemical fertilizers among small scale farmers in Ghana.…”
Section: Introductionmentioning
confidence: 96%